Output-Based Pay: Incentives, Retention or Sorting? - Edward P. Lazear (Institute for the Study of Labor (IZA), 2003)
Variable pay, defined as pay that is tied to some measure of a firm?s output, has become more important for executives of the typical American firm. Variable pay is usually touted as a way to provide incentives to managers whose interests may not be perfectly aligned with those of owners. The incentive justification for variable pay has well-known theoretical problems and also appears to be inconsistent with much of the data. Alternative explanations are considered. One that has not received much attention, but is consistent with many of the facts, is selection. Managers and industry specialists may have information about a firm?s prospects that is unavailable to outside investors. In order to induce managers to be truthful about prospects, owners may require managers to ?put their money where their mouths are,? forcing them to extract some of their compensation in the form of variable pay. The selection or sorting explanation is consistent with the low elasticities of pay to output that are commonly observed, with the fact that the elasticity is higher in small and new firms, with the fact that variable pay is more prevalent in industries with very technical production technologies, and with the fact that stock and stock options are a larger proportion of total compensation for higher level employees. The explanation fits small firms and start-ups better than larger, well-established firms.
Keywords: J3; 330; incentives; sorting; selection; Leistungsorientierte Vergütung; Führungskräfte; Leistungsanreiz; Theorie